Nutritive value of Melilotus officinalis ecotypes from the North-western Moroccan pastures - Lahkim Bennani M.; Ayadi M.; Aarab A.; Brigui J. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Twenty ecotypes of Melilotus officinalis (L.) Pall. (yellow sweet clover) were collected from the Northwestern pastures of Morocco, and then cultivated in the experimental station of INRA in Tangier. The harvesting was realized during the vegetative, budding and flowering stages in order to study their nutritive value. The results indicate that nutritive value of M. officinalis depends significantly on the vegetative stage of sampling and the ecotype origin. From the vegetative to the flowering stage, the ash content decreases from 14.01 to 8.60% on dry matter (DM) (P<0.001), from 5.76 to 2.90% DM for ether extract or fat (FM), from 19.43 to 14.51% DM for crude protein (CP). However, the content of indigestible fibers increases significantly (P<0.001) from 3.50 to 6.65% DM for lignin (ADL). Otherwise, the content of nutritive value was very highly affected by the origin of ecotypes (P<0.001). They varied between 15.99% and 18.41%DM, 10.20% and 13.48% DM, 3.46% and 5.51% DM, 7.23% and 2.46% DM respectively for CP, ash, FM and ADL. Considering its adaptation to local environmental conditions of the north-west and its high nutritive value, the selected ecotypes of M. officinalis can contribute to improve the quality and quantity of proteins for animal breeding in the region.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)